(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVE: The purpose of this study was to analyze dental caries experience of adults living in the southeastern state of São Paulo, Brazil, according to some socio-demographic conditions of this population. MATERIAL AND METHODS: The sample consisted of 1,159 school teachers and workers (35 to 44 years old) from 29 cities of the state of São Paulo, Brazil. RESULTS: 92.3% were dentate and the DMFT index (number of decayed, missing and filled teeth) was 21.0 and the mean number of decayed teeth was 1.1, with no significant difference among adults from regions with and without fluoridation. Male subjects presented the highest mean values of "D" (decayed teeth) and "M" (missing teeth) components. The percentage of caries-free subjects was higher among white subjects, as well as the mean number of teeth present in the mouth. The mean values of the "F" component (filled teeth) [9.81] and present teeth [19.3] were higher for adults from fluoridated water regions. CONCLUSIONS: In this study, the worse condition observed was the early tooth loss in all groups. In addition, people with worse socio-demographic conditions had worse oral health conditions. It is expected that oral health programs targeted to this population could be established with the goal of improving the oral health conditions of this population and hence the maintenance of the teeth for a longer period in function.